2014
DOI: 10.1089/pho.2014.3722
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Discoloration Induced by Endodontic Phenothiazine Dyes in Photodynamic Therapy

Abstract: It can be concluded that both methylene blue and toluidine blue dyes cause tooth discoloration, and that Endo-PTC cream associated with 2.5% NaOCl effectively remove these dyes, regardless of the pre-irradiation time used for PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 23 publications
2
27
1
2
Order By: Relevance
“…Values of L*, a* and b* were collected, as they were needed in the formula used to calculate the ∆E, which represents the constant difference in colour, regardless of the location in the colour space (Figueiredo et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Values of L*, a* and b* were collected, as they were needed in the formula used to calculate the ∆E, which represents the constant difference in colour, regardless of the location in the colour space (Figueiredo et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…, Figueiredo et al . ). In the present study, most ∆E values in both groups were above 3.7, which are considerable values that were easily perceptible.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The photodynamic approach to kill bacteria is a rapidly emerging alternative to current antimicrobial agents, and it is unlikely that bacteria could develop resistance to the action of ROS and 1 O 2 [35]. Previous studies reported that Enterococcus faecalis was sensitive to the lethal PDI mediated by a wide variety of PSs, including methylene blue [12,34], toluidine blue [12], cationic porphyrins [29], hypericin [22], eosin-Y, rose gengal, and curcumin [28].…”
Section: Introductionmentioning
confidence: 99%